Virtual Tour Museum Kars Indonesia Sebagai Media Alternatif Pembelajaran Sejarah - Wiganingrum, Anditya; Djono, Djono; Musadad, Akhmad Arif (Universitas Galuh, 2025)
Technology development has a significant impact on innovation in the development of museum education services, including virtual museum tours. One of the functions of the museum is as a source of virtual learning supported by visual, and audiovisual teaching materials, and interactive communication. Presenting the museum experience in the classroom online can be an alternative solution that is interesting, effective, and fun in developing learning media. The Indonesian Karst Museum is one of the treasures owned by prehistoric museums in Indonesia, especially in Central Java Province, beside the Sangiran Museum. This museum is an educational museum that presents the distribution of karst both in Indonesia and around the world. This museum displays how karst was formed, as well as the characteristics and phenomena of karst, reviewing its relationship to the evolution of human life from prehistoric times to the present. The Indonesian Karst Museum was established to preserve the existence of the Eco Karst area and the Gunung Sewu Global Geopark. Optimizing the virtual tour of the Indonesian Karst Museum as an alternative medium for learning history is expected to be an effective solution in developing a history learning medium that is easily accessible to students. This aims to introduce museums to students amidst the limitations of direct visits.